Martian sub-surface ionising radiation: biosignatures and geology - J. M. Ward; L. Desorgher; L. R. Dartnell; A. J. Coates (Biogeosciences, 2007)
The surface of Mars, unshielded by thick atmosphere or global magnetic field, is exposed to high levels of cosmic radiation. This ionising radiation field is deleterious to the survival of dormant cells or spores and the persistence of molecular biomarkers in the subsurface, and so its characterisation is of prime astrobiological interest. Here, we present modelling results of the absorbed radiation dose as a function of depth through the Martian subsurface, suitable for calculation of biomarker persistence. A second major implementation of this dose accumulation rate data is in application of the optically stimulated luminescence technique for dating Martian sediments. We present calculations of the dose-depth profile in the Martian subsurface for various scenarios: variations of surface composition (dry regolith, ice, layered permafrost), solar minimum and maximum conditions, locations of different elevation (Olympus Mons, Hellas basin, datum altitude), and increasing atmospheric thickness over geological history. We also model the changing composition of the subsurface radiation field with depth compared between Martian locations with different shielding material, determine the relative dose contributions from primaries of different energies, and discuss particle deflection by the crustal magnetic fields.